Hubungan Antara Harga Diri Dan Kecenderungan Kecanduan Smartphone Pada Ibu Rumah Tangga Di Kota Makassar - Wahdah Islamiyah Ugibojo; Basti Tetteng; Ahmad Yasser Mansyur (CV. Ulil Albab Corp, 2023)
An addicted smartphone can disrupt interpersonal relationships, health, and activities in daily life. One of the causes of smartphone addiction is low self-esteem. The purpose of this study was to determine the relationship between self-esteem and the tendency toward smartphone addiction in housewives in Makassar City. This research uses quantitative methods. The subjects in this study were 220 housewives in Makassar City, using the technique of accidental sampling. The technique used in hypothesis testing is spearman rho to examine the correlation between self-esteem and the tendency toward smartphone addiction. The results of the research on hypothesis testing showed that the significance value was p = 0.000 (p < 0.05), and the correlation coefficient value was -0.461. Thus, among housewives, there is a significant relationship between self-esteem and tendencies toward smartphone addiction. The correlation value shows a negative value, which means self-esteem and addiction tendencies are negatively correlated and included in the medium category. The negative correlation value indicates that the lower the housewife's self-esteem in Makassar City, the higher the level of addiction tendencies to smartphones. The results of this study are expected to be used as evaluation material for individuals to be more efficient and effective in utilizing smartphone